Faktor Faktor Yang Berhubungan Dengan Stres Kerja Customer Service Di PT Telekomunikasi Indonesia,Tbk Lampung Tahun 2019 - Abdul Wakhid; Endang Budiati (JIKMI (Jurnal Ilmu Kesehatan Masyarakat Indonesia), 2020)
AbstractExcessive stress can cause a person unable to think clearly in action and difficult to make the right decision. In Australia only 37% of workers do good work by managing stress well but in Indonesia, 40% of cases in and out of workers are due to stress. Customer service is the most vulnerable part of being stressed because it is required to always be professional. This research used a cross sectional design. The research sample are 32 respondents with total sampling technique. Data analysis using univariate and bivariate. For bivariate use the chi-quere test. The results showed that there is a correlation between workload and work stress P Value = 0.036 and OR = 6,500 and there is a correlation between years of work and work stress P Value = 0.006 and OR = 12,500. recommend for PT Telekomunikasi Indonesia, Tbk Lampung to check physical and mental health of workers, before and after the work period to monitor work stress experienced by workers. High workload, it is recommended to give a lot of motivation and recreation.Keywords : Work Stress, Workload, Work Period.